Modul Sains Komik (MOSAKO) berbasis Science Technology Engenering and Mathematic (STEM) untuk Siswa Sekolah Dasar - Winarto Winarto; Diyah Ayu Retnoningsih; Dwi Hesty Kristyaningrum (Khazanah Pendidikan, 2021)
The results of education in Indonesia are considered unsuccessful, especially at the primary and secondary levels. The Program for International Students Assessment (PISA) assessment of the literacy abilities (mathematics, science, and language) of students from around the world respectively in 2003, 2006, 2009 and 2012. The purpose of this study was to develop a science comic module media approach. STEM for grade V students. This type of research is Research and Development (R&D) research. The development model used is 4D from Thiagarajan (1974). The sample technique used is purposive sampling. Data collection techniques using interviews, questionnaires and tests. Data analysis using descriptive statistics. The research results obtained (1) MOKOSA media needs to be developed based on a preliminary study, there is no media that packs comics and STEM. (2) STEM-based MOKOSA is feasible and valid based on the results of media validation, material and student responses with very good categoriesKeywords: Development, MOSAKO, STEM, Literacy, Elementary School